Framework computacional para programação de produção de capacidade finita - Pereira, Valdecir de Oliveira (2013)
The current competitive environment leads companies to produce better, faster and at lower cost. To keep ahead of your competition, it is necessary to use tools that can help in decision making. In this context, a production planning software can contribute to success. In this scenario, the proposed framework can provide a basic infrastructure for software development that can meet the demands of the current production systems and it can be extended to satisfy other requirements. A prototype software was developed as reference to the proposed framework. In this application, some dispatching rules and genetic algorithms were developed aiming better results. The system was deployed in a mold industry and the results indicate that it could be a good alternative to improve production performance.